MODEL OPTIMALISASI DAYA SAING DAN SINERGIVITAS KINERJA UMKM DI JEPARA - Sarwido Sarwido; Dwi Sulistyawati Retno Sulistyawati (Jurnal DISPROTEK, 2014)
ABSTRACT By tackling the issue of SMEs remains piecemeal and not comprehensive, comprehensive and simultaneous. Due to lacking of coordination between agencies related to SME development led to many SMEs entangled bad credit and even go out of business. In the meantime, the existence of SMEs is very important to support the national economy and create jobs and prosperity. This study is based on the problems faced by SMEs over the years, both the problems associated with the condition of internal and external conditions, among others, field operations, processing, marketing, capital, human resources, technology, business climate or competition . This research can generally be concluded that based on the results obtained endorsement of hypothesis testing positive and significant that reinforce the concept that SME performance improvement can be achieved through internal factors, external factors, barriers to innovation and partnership capabilities. Although the magnitude of the effect is not the same but overall indicate a significant influence. Keywords : Internal and External Factors, Capability, Obstacles, Performance of SMEs ABSTRAK Dengan memegang pokok masalah SMEs menyisakan sedikit demi sedikit, tidak menyeluruh dan berkesinambungan. Karena kurangnya koordinasi antara agensi terkait dengan perkembangan SMEs menimbulkan banyak SMEs terlibat bad credit, bahkan bangkrut. Sementara itu keberadaan SMEs sangat penting untuk mendukung ekonomi nasional dan menciptakan lapangan pekerjaan serta kemakmuran. Studi ini berdasarkan masalah yang dihadapi oleh SMEs bertahun-tahun, kedua masalah terkait dengan kondisi internal dan eksternal, diantara yang lainnya, operasi lapangan, proses, pemasaran, modal, SDM, teknologi, iklim bisnis atau kompetisi. Penelitian ini umumnya dapat disimpulkan bahwa hasil dari tes dukungan hipotesis adalah positif dan signifikan bahwa menguatkan konsep perbaikan performans SME bisa dicapai melalui faktor internal, faktor eksternal, dari rintangan ke arah inovasi dan kemampuan partnership. Walaupun besarnya dampak itu tidak sama tapi semuanya mengindikasikan pengaruh signifikan. Kata kunci: faktor internal dan eksternal, kapabilitas, rintangan, performans SMEs